2014
DOI: 10.1073/pnas.1412449111
|View full text |Cite
|
Sign up to set email alerts
|

Putative chanzyme activity of TRPM2 cation channel is unrelated to pore gating

Abstract: Transient receptor potential melastatin 2 (TRPM2) is a Ca 2+ -permeable cation channel expressed in immune cells of phagocytic lineage, pancreatic β cells, and brain neurons and is activated under oxidative stress. TRPM2 activity is required for immune cell activation and insulin secretion and is responsible for postischemic neuronal cell death. TRPM2 is opened by binding of ADP ribose (ADPR) to its C-terminal cytosolic nudix-type motif 9 (NUDT9)-homology (NUDT9-H) domain, which, when expressed in isolation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 28 publications
4
60
0
Order By: Relevance
“…The C-termini of TRPM2, TRPM6, and TRPM7 channels possess enzymatic domains and have been named "chanzymes" [136][137][138][139]. Similar to TRPC4/C5 channels, TRPM channels possess disulfide bonds at their extracellular pore that stabilize the pore domain, but these disulfide-bonds form between cysteines at the pore loop and the pore helix S6 [119].…”
Section: Trpc and Trpm Channelsmentioning
confidence: 99%
“…The C-termini of TRPM2, TRPM6, and TRPM7 channels possess enzymatic domains and have been named "chanzymes" [136][137][138][139]. Similar to TRPC4/C5 channels, TRPM channels possess disulfide bonds at their extracellular pore that stabilize the pore domain, but these disulfide-bonds form between cysteines at the pore loop and the pore helix S6 [119].…”
Section: Trpc and Trpm Channelsmentioning
confidence: 99%
“…The single atom substitution in the methylene bis-phosphonate analogue AMPCPR corresponded to a roughly 40 fold reduction in potency at hTRPM2 and AMPCPR is also only a partial hTRPM2 agonist. 22 Alternatively the substitution of the pyrophosphate with the phosphonoacetate bioisostere may alter the presentation of other critical binding partners in the hTRPM2 binding pocket. Our molecular modelling suggests the phosphonoacetate linker theoretically seems to be a very good spatial mimic of the pyrophosphate unit, with sufficient exibility to allow the adenosine and terminal ribose binding partners to position themselves in the same orientation as ADPR (ESI, Fig.…”
Section: Biological Evaluation Of 1 Andmentioning
confidence: 99%
“…21 Tóth et al showed that AMPCPR still supports TRPM2 channel gating, albeit as a lower affinity partial agonist. 22 AMPCPR has been used to uncouple the TRPM2 channel gating mechanism from its enzymatic activity by virtue of its pyrophosphatase resistant methylene bis-phosphonate linker. 22,23 Two further ADPR analogues with similarly modied pyrophosphates (one methylene bisphosphate and one diuoromethylene bisphosphate, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the important cell biology question of which agonist directly activates TRPM2 is the goal of an elegant new report in the May 2015 issue of The Journal of General Physiology by Tóth, Iordanov, and Csanády ( Tóth et al, 2015 ). Previous work by this group determined that enzymatically purified AMP and cADPR added to inside-out excised membrane patches did not, in fact, activate TRPM2 ( Tóth et al, 2014 ). Using available commercial tools, such as a linear nucleotide-specific pyrophosphatase, the authors showed that apparent TRPM2 activation by cADPR was actually caused by the presence of contaminant ADPR ( Tóth and Csanády, 2010 ).…”
Section: A New Study Reveals the True Nature Of Trpm2 Activatorsmentioning
confidence: 99%